REGULATION OF CONSULTING SERVICES BASED ON DIGITAL TECHNOLOGIES: CIVIL LAW ASPECTS - Shahriddin Fakhriddin Ugli Asadov (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the civil legal framework regulating consulting services based on digital technologies, with a focus on the legal challenges emerging from the transition from traditional to digital platforms in Uzbekistan. Method: Employing systematic, comparative legal, and statistical analyses, the research examines electronic contracts, the rights and obligations of parties, and mechanisms for dispute resolution within the context of Uzbekistan's